Consuming dance choreography and advertising - Dunagan, Colleen T. 1971- (Oxford University Press, 2018)
Whether advertising clothes or technology, dance is a staple of advertising today. Consuming Dance offers a clear history and analysis of dance in advertising and demonstrates the ways in which the form articulates with, informs, and reflects U.S. culture